2020
DOI: 10.1136/bmjopen-2019-035650
|View full text |Cite
|
Sign up to set email alerts
|

Incremental yield of ECG screening repeated annually over 4 years in an adult Japanese population without prior atrial fibrillation: a retrospective cohort study

Abstract: ObjectivesInternational guidelines recommend opportunistic screening for atrial fibrillation (AF); however, there is no current data to inform how often to repeat screening. We aimed to investigate the incremental annual yield and stroke risk of new AF cases in individuals screened annually over 4 years.DesignA retrospective cohort study.SettingHokuriku Health Service Association, Toyama prefecture, Japan.ParticipantsEmployees and their families receiving annual health examinations from Hokuriku Health Service… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
13
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
7
1

Relationship

5
3

Authors

Journals

citations
Cited by 10 publications
(14 citation statements)
references
References 28 publications
(38 reference statements)
1
13
0
Order By: Relevance
“… 21 In addition, in Japan, employers have a legal obligation to provide annual health examinations that include a 12‐lead ECG to employees and their families. 22 For nonemployed or retired residents, the government provides access to annual health examinations, although attendance is optional. Therefore, patients diagnosed at medical screening would be less likely to be symptomatic, have a severe substrate, and have impaired HRQoL, than those diagnosed at the clinic or emergency room.…”
Section: Discussionmentioning
confidence: 99%
“… 21 In addition, in Japan, employers have a legal obligation to provide annual health examinations that include a 12‐lead ECG to employees and their families. 22 For nonemployed or retired residents, the government provides access to annual health examinations, although attendance is optional. Therefore, patients diagnosed at medical screening would be less likely to be symptomatic, have a severe substrate, and have impaired HRQoL, than those diagnosed at the clinic or emergency room.…”
Section: Discussionmentioning
confidence: 99%
“…However, several studies suggested the existence of racial differences in the risk of AF. For example, one previous report from Japan suggested a lower incidence of AF in Japanese people as compared with western populations 12. Consistent with this notion, it has been reported that a single screening of subjects over 65 years of age from western countries was likely to yield 1.44% persons with new- onset AF,13 whereas a study from Japan reported identifying new-onset AF in only 0.45% (95% CI 0.30% to 0.64%) of persons with a mean age of 65 years and above 12.…”
Section: Discussionmentioning
confidence: 99%
“…For example, one previous report from Japan suggested a lower incidence of AF in Japanese people as compared with western populations 12. Consistent with this notion, it has been reported that a single screening of subjects over 65 years of age from western countries was likely to yield 1.44% persons with new- onset AF,13 whereas a study from Japan reported identifying new-onset AF in only 0.45% (95% CI 0.30% to 0.64%) of persons with a mean age of 65 years and above 12. Considering that previous studies consistently reported a 1.3-fold to 1.6-fold higher risk of AF in patients with T2D,9 10 the incidence rate of AF in our elderly patients with T2D (5.14/1000 PY) seemed quite consistent with previous reports.…”
Section: Discussionmentioning
confidence: 99%
“…Similar results were reported on annual repeat screening in Japan. 23 The STROKESTOP study showed incremental yield with more intensive screening using twice daily, handheld ECG recordings for 2 weeks. 16 Given that AF is often paroxysmal, repeated or more intensive screening is likely to diagnose more AF than single time-point screening, but the stroke risk may be lower, especially with long-term continuous recordings.…”
Section: Discussionmentioning
confidence: 99%